Longitudinal growth of mammalian bones: a possible role for membrane transporters in mediating chondrocyte hypertrophy - Mohamad Yusof, Loqman; Yusof, Loqman Mohamad (The University of Edinburgh, 2012)
Long bone lengthening occurs at the growth plate (GP) by well-regulated chondrocyte proliferation, hypertrophy and terminal matrix deposition. GP chondrocyte (GPC) hypertrophy has been implicated to be the main determinant of bone growth rate; however the mechanism is poorly understood. The work of this thesis examined some of the cellular process that drives the chondrocyte swelling or hypertrophy particularly in a mammalian post natal GPs using living in situ GPC and fixed GP tissues. Confocal scanning microscopy (CLSM) was used to determine living in situ GPC volume and dimension changes in proliferative zone (PZ) through to hypertrophic zone (HZ) chondrocytes of different GPs of various bones. While PZ cells showed similar volumes and dimensions, HZ cells varied in different GPs, even within the same long bone but at opposite ends. However, the hypertrophic cell volume measured at a single post natal age (day 7) was independent of the corresponding bone length. This could reflect a complex interplay between local and systemic factors in different GPs, which occurs throughout the active phase of bone growth. Maintaining GPC morphology was critical in studying GPC hypertrophy using fixed tissues. This work highlighted a problem caused by conventional fixative solutions, which caused up to 44% hypertrophic GPC shrinkage following GP fixation. This artifact appeared to be associated with the hyperosmotic nature of the fixatives used and could be abolished by adjusting the fixative osmolarity close to physiological level (280 mOsm), or could be significantly reduced by bisecting bone tissues prior to tissue fixation. This thesis proposed roles for plasma membrane transporter(s) in mediating GPC hypertrophy. This hypothesis was tested by examining roles of sodium-hydrogen exchanger (NHE) and anion exchanger (AE) in GPC hypertrophy using an ex vivo bone growth inhibition model. Inhibition of bone growth by inhibitors of NHE (EIPA) and AE (DIDS) respectively was shown to be dose-dependent. The histology of bones demonstrated that the late HZ width was significantly reduced in GPs treated with EIPA or DIDS. Although in situ GPC volumes in the PZ and HZ were not notably different in DIDS-treated GP, the cell volumes in both zones were significantly reduced by EIPA treatment. Fluorescence immunohistochemistry revealed distinctive cellular localisations of NHE1 and AE2 in the PZ and early HZ. These results suggest a possible role of AE in mediating GPC volume increase in PZ chondrocytes and those in the early stages of cell hypertrophy, whereas NHE could possibly maintain intracellular pH of GPC throughout all GP zones. This thesis has characterized various changes in volume and dimensions of living in situ GPC from PZ through to HZ of different GPs of postnatal rats. This work emphasized the importance of fixative osmolarity in order to accurately preserve the normal volume/morphology of cells within tissues. Most importantly, this thesis confirmed a potential role of the plasma membrane transporters, AE and NHE in GPC hypertrophy of growing bones.
Keywords: longitudinal growth; membrane transporter; chondrocyte hypertrophy